1990
DOI: 10.1002/j.1460-2075.1990.tb08274.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 replication is controlled at the level of T cell activation and proviral integration.

Abstract: During progression of the Acquired Immune Deficiency Syndrome (AIDS), the human immunodeficiency virus type 1 (HIV‐1) is harbored in CD4+ T cells, which act as the primary reservoir for the virus. In vitro, HIV‐1 requires activated T cells for a productive infection; however, in vivo, the number of circulating T cells in the activated state that are potential targets for HIV‐1 infection is low. We have investigated the ability of HIV‐1 to infect resting T cells, and the consequences of such an infection. T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
551
5
7

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 741 publications
(591 citation statements)
references
References 50 publications
28
551
5
7
Order By: Relevance
“…However, although exogenous stimulation of dNTP levels enhanced reverse transcription and generation of full-length transcripts, this did not overcome the block to infection. These and other studies (22,26) support the notion that a block subsequent to reverse transcription prevents productive infection of quiescent lymphocytes. Upon infection of monocytes, reverse transcription was highly inefficient when analyzed up to 66 h postinfection and was not improved by normalization of dNTP levels (Fig.…”
supporting
confidence: 78%
“…However, although exogenous stimulation of dNTP levels enhanced reverse transcription and generation of full-length transcripts, this did not overcome the block to infection. These and other studies (22,26) support the notion that a block subsequent to reverse transcription prevents productive infection of quiescent lymphocytes. Upon infection of monocytes, reverse transcription was highly inefficient when analyzed up to 66 h postinfection and was not improved by normalization of dNTP levels (Fig.…”
supporting
confidence: 78%
“…From the data in Table 1, HIV replication fold over non-stimulated PBLs at 72 h Syncytia formation in non-stimulated and stimulated PBLs as measured by the infected centers assay (see Materials and methods). a Syncytia/10 4 cells (Stevenson et al, 1990;Zack et al, 1990). In activated T cells, the viral DNA is integrated and HIV replication depends on viral accessory proteins and host factors (Cullen, 1998;Finzi and Silliciano, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…MLV-based vectors, on the other hand, were quite inefficient and never transduced more than 1% of the cells. We demonstrated that eGFP detection in HVS-T cell lines transduced with HRSIN-CSGW represents vector transduction (and not pseudotransduction 16 or expression from nonintegrated vectors 17,18 ) since the percentage of eGFP þ cells remained stable for at least 48 days as shown in Figure 2. This also supports that gene silencing 19 is not occurring in lentiviral-transduced HVS-T cells.…”
Section: Discussionmentioning
confidence: 84%
“…This is important since transgene detection in target cells may be due to pseudotransduction 16 (especially at high MOIs) or expression from nonintegrated vectors. 17,18 Additionally, the expression of the transgene by transduced cells can be blocked by gene silencing. 19 The expression of eGFP protein was determined on days 7, 28 and 48 after a single round of cell transduction on day one.…”
Section: Cell Transduction and Vector Titrationmentioning
confidence: 99%